REVIEW OF REALIZATION OF THREE PHASE TWO STAGE GRID SYSTEM BY USING LLC RESONANT CONVERTER - Mr.Bhooshan Dileep Darkonde; Prof.Prabhodhkumar Khampariya (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Module integrated converters (MICs) in single phase have witnessed recent market success because of unique features such as improved energy harvest, improved efficiency of the system, lower installation costs, plug-and play operation, and enhanced flexibility and modularity. A niche market has been grown by the MIC sector to mainstream, especially in the United States. Assuming further expansion of the MIC market, this paper presents the micro inverter concept incorporated in large size photovoltaic (PV) installations such as megawatts (MW)-class solar farms where a three-phase ac connection is employed. A high-efficiency three-phase MIC with two-stage zero voltage switching (ZVS) operation for the grid-tied PV system is proposed which will reduce cost per watt, improve re-liability, and increase scalability of MW-class solar farms through the development of new solar farm system architectures. The first stage mainly considered for a high efficiency full-bridge LLC resonant dc–dc converter which interfaces to the PV panel and produces a dc link voltage. A center point’s iteration algorithm developed specifically for LLC resonant topologies is used to track the maximum power point by the PV panel. The second stage is comprised of a three-phase dc–ac inverter circuit which employs a simple soft-switching scheme without adding auxiliary